Percutaneous Ilio-Sacral Screw Fixation in Supine Position under Fluoroscopy Guidance - Shrestha, D; Dhoju, D; Shrestha, R; Sharma, V (Kathmandu University Medical Journal, 2015)
Background Pelvic ring disruption when treated conservatively can be associated with prolonged hospital stay and immobilization, mal-union, chronic pain, limb length discrepancy if they are treated conservatively. Open reduction and fixation in an already compromised soft tissue and hemodynamically unstable patient causes more soft tissue injury, heamatoma, infection and neurovascular injury. Percutaneous ilio-sacral joint fixation can be an alternative technique for sacro-iliac joint injury and sacral fracture. Objective To evaluate technique and safety of percutaneous ilio-sacral screw fixation in supine position under single fluoroscopy guidance for sacral fracture and sacro-iliac joint disruption. Method Twenty one patients either with sacral fracture or sacro-iliac joint disruption with percutaneous ilio-sacral screw fixation with cannulated cancellous screw fixation in between 2008 to 2014 were retrospectively evaluated including AP, inlet and outlet views of pelvis X rays and CT scan. Tile’s classification and Dennis classification were used for pelvis and sacral injury. Result Thirty five percutaneous ilio-sacral screws were placed (Male: 6, Female: 15; range: 15 to 54) for sacral fracture involving zone 2 (8 with sacral fracture only and 5 with pelvis injury; Tile’s type B in four and type C in one) and sacro-iliac joint injury (Tile’s type B in three and type C in five). Commonest mode of injury was motor vehicle accidents (10) followed by fall related injury (6). Injury hospital interval and injury surgery interval was five hours to 13 days and 2 to 20 days respectively. Follow period was 3 months to 6 years. One patient developed post-operative deep vein thrombosis and another patient had post-operative haematoma. Two screws were juxtra-foramial. Good to excellent outcome were in 16 patients, fair in four and poor in one patient (Majeed Scoring). Conclusion Percutaneous ilio-sacral screw fixation for sacro-iliac joint injury and sacral fracture with C arm guidance is safe and minimally invasive technique. Clear images and accurate interpretation of X-rays, CT scans and per operative C arm images are important to avoid malpositioning of screws and iatrogenic neurovascular injuries. Kathmandu University Medical Journal Vol.13(1) 2015; 56-60